KAJIAN KINERJA PEGAWAI BERDASARKAN KEPEMIMPINAN, KOMUNIKASI, DAN KONFLIK KERJA (Studi Kasus di Kantor BAPPEDA Kabupaten Pidie) - Handayani, Sri; Syahriani, Endang (IndOmera, 2026)
This study examines the impact of several factors on employee performance at the Regional Development Planning Agency (Bappeda) office in Pidie Regency, Aceh. The factors involved are leadership, communication, and work conflict. This study uses an associative quantitative research method and path analysis. The empirical results show: (1) leadership, communication, and work conflict have a direct and combined influence on employee performance, amounting to 45.53%, 46.92%, and 40.19%, respectively. (2) The contribution of leadership, communication, and work conflict to employee performance is quite significant, amounting to 47,8%. (3) The three factors, leadership, communication, and work conflict—have a causal relationship with a fairly strong categorization.